2014
DOI: 10.1038/leu.2014.135
|View full text |Cite
|
Sign up to set email alerts
|

piRNA-823 contributes to tumorigenesis by regulating de novo DNA methylation and angiogenesis in multiple myeloma

Abstract: Aberrant DNA hypermethylation contributes to myelomagenesis by silencing tumor-suppressor genes. Recently, a few reports have suggested that a novel class of small non-coding RNAs, called Piwi-interacting RNAs (piRNAs), may be involved in the epigenetic regulation of cancer. In this study, for the first time we provided evidence that the expression of piRNA-823 was upregulated in multiple myeloma (MM) patients and cell lines, and positively correlated with clinical stage. Silencing piRNA-823 in MM cells induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
168
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(179 citation statements)
references
References 55 publications
4
168
0
Order By: Relevance
“…Correspondingly, piRNAs have important roles in mRNA regulation in the mouse by rendering targeting specificity (6,43). Furthermore, some previous researchers suggested that piRNAs have independent functions, such as piR-823 having a role in breast cancer (5). Our analysis indicates that a small number of piRNAs are expressed in MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Correspondingly, piRNAs have important roles in mRNA regulation in the mouse by rendering targeting specificity (6,43). Furthermore, some previous researchers suggested that piRNAs have independent functions, such as piR-823 having a role in breast cancer (5). Our analysis indicates that a small number of piRNAs are expressed in MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 69%
“…liush@shanghaitech.edu.cn. 5 The abbreviations used are: PIWI, P-element-induced wimpy testis; piRNA, PIWI-interacting RNA; TNBC, triple-negative breast cancer; miRNA, microRNA. …”
mentioning
confidence: 99%
“…However, few literatures are available. piR-823 was found to contribute to tumorigenesis by regulating de novo DNA methylation and angiogenesis in multiple myeloma [66]. piR-932 was suggested to bind PIWIL2 to promote the methylation of Latexin in breast cancer stem cells [61].…”
Section: Piwi-interacting Rnas Are Related To Tumorigenesismentioning
confidence: 99%
“…The inhibited expression of piRNA-823 in MM cells significantly reduced DNMT3A and 3B at both mRNA and protein levels, which in turn led to decrease in global DNA methylation and reexpression of methylation-silenced tumor suppressor, p16INK4A. In addition, piRNA-823 abrogation in MM cells reduced vascular endothelial growth factor secretion, accompanied by decreased proangiogenic activity, suggesting an oncogenic role of piRNA-823 in the biology of MM [77]. Jacobs et al [78] utilized directly measured and imputed genotypes from the GliomaScan genome-wide association study (GWAS) to analyze piRNAs associated with glioma risk and the results revealed that piR-598 impacted cell survival and reduced glioma cell viability and colony formation, which sharply promoted cell proliferation.…”
Section: Introductionmentioning
confidence: 99%